External cooling efficiently controls intraosseous temperature rise caused by drilling in a drilling guide system: an in vitro study. Issue 10 (December 2015) - Boa, Kristof; Varga, Endre; Pinter, Gabor; Csonka, Akos; Gargyan, Istvan; Varga, Endre
Abstract: The purpose of this study was to measure the rise in intraosseous temperature caused by drilling through a drilling guide system. We compared the rise in temperature generated, and the number of increases of more than 10 °C, between drills that had been cooled with saline at room temperature (25 °C) and those that had not been cooled, for every step of the drilling sequence. Cortical layers of bovine ribs were used as specimens, and they were drilled through 3-dimensional printed surgical guides. Heat was measured with an infrared thermometer. The significance of differences was assessed with either a two-sample t test or Welch's test, depending on the variances. The mean rises (number of times that the temperature rose above10 °C) for each group of measurements were: for the 2 mm drill, 4.8 °C (0/48) when cooled and 7.0 °C (8/48) when not cooled; with the 2.5 mm drill, 5.2 °C (1/48) when cooled and 8.5 °C (17/48) when not cooled (2 mm canal); with the 3 mm drill, 3.3 °C when cooled (0/48) and 8.5 °C (18/24) when not cooled (2.5 mm canal); and with the 3.5 mm drill, 4.8 °C when cooled (0/24) and 9.4 °C when not cooled (10/23) (3 mm canal). The temperature rose significantly less with cooling at every step of the drilling sequence (p<0.001). We conclude that external cooling can maintain the intraosseous temperature within the safe range while drilling through an implant guide system, whereas drilling without irrigation can lead to temperatures that exceed the acceptable limit.